Cyclization–Carbonylation–Cyclization Coupling Reactions of N-Propargylanilines and o-Alkynylphenols with Palladium(II)–Bisoxazoline Catalysts - Kusakabe, Taichi; Sekiyama, Emika; Ishino, Yukari; Motodate, Satoshi; Kato, Shigeki; Mochida, Tomoyuki; Kato, Keisuke (Synthesis, 2012)
Cyclization–carbonylation–cyclization coupling reactions (CCC-coupling reactions) of N-propargylanilines and o-alkynylphenols catalyzed by (box)Pd(II) complexes afforded symmetrical bis(quinolin-3-yl) and bis(benzofuran-3-yl) ketones, respectively, in moderate to excellent yields.
Keywords: palladium; tandem reaction; carbonylation; alkynes; dimerization